2021
DOI: 10.1007/s11249-021-01546-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cylinder Liner Microstructure on Lubrication Condition of a Twin-Land Oil Control Ring and a Piston Skirt of an Internal Combustion Engine

Abstract: It is hypothesized that the sliding surface structures improve the lubrication condition by forming an oil sump on the sliding surface, redistributing the oil, and trapping wear debris. For these reasons, the sliding surface structures have been used as a friction reduction method for a long time. However, how to optimize the sliding surface structure is still controversial. In this work, effects of microstructure laid on the cylinder liner of an internal combustion engine on twin-land oil control ring (TLOCR)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…In [146], the effect of microstructure laid on the cylinder liner of an internal combustion engine on the lubrication condition of the control ring was investigated. Measurements using a floating sleeve engine showed that the microstructure improved lubrication conditions by reducing hydrodynamic Among all these methods, surface texturing has become one of the main methods to improve the tribological properties of mechanical pairs undergoing relative sliding motion.…”
Section: Components Of Dust Percent By Weight [%]mentioning
confidence: 99%
“…In [146], the effect of microstructure laid on the cylinder liner of an internal combustion engine on the lubrication condition of the control ring was investigated. Measurements using a floating sleeve engine showed that the microstructure improved lubrication conditions by reducing hydrodynamic Among all these methods, surface texturing has become one of the main methods to improve the tribological properties of mechanical pairs undergoing relative sliding motion.…”
Section: Components Of Dust Percent By Weight [%]mentioning
confidence: 99%
“…A number of studies have been conducted to investigate the losses of various oil control ring types. Two-piece oil control rings have been investigated by Profito et al [1], Söderfjäll et al [2,3], Liu et al [4], Westerfeld et al [5] and Kikuhara et al [6]. Profito et al [1] used a numerical tribological model to show that an increased hydrodynamic load carrying capacity was achieved after the cylinder liners were run-in for an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
“…The authors noted that higher sliding speeds were required for the three-piece oil control rings to achieve transition to full hydrodynamic lubrication than for the equivalent two-piece oil control rings. Kikuhara et al [6] showed that surface texturing of the cylinder bore/liner surface could, under some operating conditions, reduce viscous frictional losses.…”
Section: Introductionmentioning
confidence: 99%
“…Etsion found a variety of surface textures that can significantly improve the performance of friction pairs [18,19]. These surface structures mainly include pit structures [20,21], groove structures [22][23][24][25][26] and other structures [27][28][29][30]. The pit structure includes circular pits, oval pits and square pits [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%